Tissue-specific expression of the human aromatase cytochrome P-450 gene by alternative use of multiple exons 1 and promoters, and switching of tissue-specific exons 1 in carcinogenesis. - Harada, N (1993)
Extensive screening of aromatase cDNA was carried out in cDNA libraries from various human tissues. The DNA sequences of all the isolated cDNA clones were identical in the region encoded by exons 2-10 of the aromatase gene. However, tissue-specific sequences, which were classified into four groups, were observed in the 5' portions of the clones corresponding to the region encoded by exon 1. All of them were also found in clones isolated from a human genomic library and mapped between exons 1 and 2 of the human aromatase gene reported previously, suggesting the presence of multiple exons 1 and promoters in the gene. Reverse transcription-PCR analyses of aromatase mRNAs in various tissues revealed that aromatase transcripts are tissue-specifically spliced by alternative use of multiple exons 1, although minor forms of the transcripts were also present in each tissue. Aromatase mRNA is spliced from 10 exons in most tissues, but from 9 exons in the prostate and from 10 or 11 exons in the placenta. This suggests that tissue-specific regulation of the aromatase gene in various tissues may be explained by alternative use of multiple exons 1 flanked with tissue-specific promoters. The alternative use of multiple exons 1 for liver transcripts was found to change developmentally. Furthermore, switch from an adipose-specific exon 1 to another type of exon 1 was observed in aromatase transcripts of adipose tissues of three of five breast cancer patients.